Pengaruh Pengalaman Kerja, Stres Kerja dan Work Life Balance Terhadap Produktivitas Karyawan pada Pt. Pacific Medan Industri (Pamin) - affandi, Amru; maganda saragih, Nahar (Maisyatuna, 2023)
This study aims to determine the effect of work experience, work stress and work life balance on employee productivity at PT. Pacific Medan industry. This research method uses quantitative methods with data collection techniques used in this study are interviews, observations and population questionnaires used are employees who work at PT. Pacific Medan Industri, with a population of 207. The number of samples drawn using the Slovin formula, the sample obtained was 68 respondents with = 0.1 . Data processing using SPSS Version 23 software, with descriptive analysis, multiple regression analysis and hypothesis testing.The results of the research variable work experience partially positive and significant effect on employee productivity at PT. Pacific Medan Industry. The results of the research variable work stress partially positive and significant effect on employee productivity at PT. Pacific Medan Industry.